The mechanics of myeloid cells. - Bashant, Kathleen R; Topefner, Nicole; Day, Christopher J; Mehta, Nehal N; Kaplan, Mariana J; Summers, Charlotte; Guck, Jochen; Chilvers, Edwin R (Wiley-Blackwell, 2020)
The effects of cell size, shape, and deformability on cellular function have long been a topic of interest. Recently, mechanical phenotyping technologies capable of analyzing large numbers of cells in real time have become available. This has important implications for biology and medicine, especially haemato-oncology and immunology, as immune cell mechanical phenotyping, immunologic function, and malignant cell transformation are closely linked and potentially exploitable to develop new diagnostics and therapeutics. In this review, we introduce the technologies used to analyze cellular mechanical properties and review emerging findings following the advent of high throughput deformability cytometry. We largely focus on cells from the myeloid lineage, which are derived from the bone marrow and include macrophages, granulocytes and erythrocytes. We highlight advances in mechanical phenotyping of cells in suspension that are revealing novel signatures of human blood diseases and providing new insights into pathogenesis of these diseases. The contributions of mechanical phenotyping of cells in suspension to our understanding of drug mechanisms, identification of novel therapeutics and monitoring of treatment efficacy particularly in instances of hematologic diseases are reviewed, and we suggest emerging topics of study to explore as high throughput deformability cytometers become prevalent in laboratories across the globe. This article is protected by copyright. All rights reserved.
Keywords: cell migration/adhesion; cell motility/contraction; disease; heart/lung/blood vessels; metastasis